?AQUATIC FUNGI IN POLLUTED MARINE WATER AND THEIR RELATIONSHIP WITH DRIED FISH (Biological Sciences - PJSIR, 2000)
The fungal flora of the polluted water and mud samplesof Pasni and Ormara coasts were investigated using baiting and plating techniques. Most of the isolated fungi were the members of Mastigomycotina, Zygomycotina and Deuteromycotina. Fungi isolated from dried fish were the same as isolated from mud and water samples. Saprolegnia parasitica, S. declina and an unidentified lower fungi recorded exclusively from dried fish samples.